2009
DOI: 10.1017/s0022149x09289371
|View full text |Cite
|
Sign up to set email alerts
|

Bird schistosome diversity in Iceland: molecular evidence

Abstract: During the years 2002-2007, Icelandic freshwater snails and birds from different orders were examined for bird schistosomes. Only the snail Radix peregra and anatid birds proved to be infected. In total, 32 samples of bird schistosome cercariae from seven localities and four samples of adults of Anas platyrhynchos and Mergus serrator from two localities were used for sequencing of the internal transcibed spacer (ITS) region of rDNA. Based on the sequence and position in the phylogenetic tree, five species/geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 26 publications
0
25
1
Order By: Relevance
“…Current results based on all of the available sequence data in GenBank for the internal transcribed spacer (ITS) region indicate that there are about nine distinct lineages, only two of which are described: Gigantobilharzia and Dendritobilharzia (40,(64)(65)(66)(67)(68)(69). Most of the lineages in this part of clade D have one to a few species and have been seen in only a few cases, many related to dermatitis outbreaks (12) ( Table 1).…”
Section: Diversity Of Schistosomes Causing Dermatitismentioning
confidence: 99%
See 1 more Smart Citation
“…Current results based on all of the available sequence data in GenBank for the internal transcribed spacer (ITS) region indicate that there are about nine distinct lineages, only two of which are described: Gigantobilharzia and Dendritobilharzia (40,(64)(65)(66)(67)(68)(69). Most of the lineages in this part of clade D have one to a few species and have been seen in only a few cases, many related to dermatitis outbreaks (12) ( Table 1).…”
Section: Diversity Of Schistosomes Causing Dermatitismentioning
confidence: 99%
“…Most of the effort has been conducted using three gene regions. To date, the nuclear ribosomal DNA D1-D2 regions of 28S, the internal transcribed spacer (ITS) region, and the mitochondrial cox1 gene have been tested as molecular markers for systematics (40,63,67,69,70,105,123,248,249,251), epidemiology (252), and diagnostics (121,253). Sequencing of gene regions such as the nuclear ITS region and the mitochondrial cox1 gene not only has linked life cycle stages but also has suggested that our recognition of the diversity of avian schistosomes continues to grow (10, 12, 40, 65-67, 69, 70, 105, 129, 133, 135).…”
Section: Detection and Identification Of Avian Schistosomesmentioning
confidence: 99%
“…Focusing on the nasal species, T. regenti, five final hosts have already been identified in France; A. platyrhynchos and A. fuligula, previously described by Rudolfová et al (2002) and Picard and Jousson (2001), and also C. olor, M. merganser and A. clypeata (Jouet et al 2009). In Iceland, recent molecular analyses of eggs and adult worms of a nasal Trichobilharzia found in A. platyrhynchos in Landmannalaugar, previously reported by Skírnisson and Kolářová (2008;Skírnisson et al 2009) and Aldhoun et al (2009) as undescribed species, have now confirmed that the involved species actually was T. regenti. Moreover, the detection of T. regenti eggs in the nasal cavity of A. anser represents a new final host record.…”
Section: Discussionmentioning
confidence: 59%
“…However, in recent years, the application of molecular markers to these parasites has significantly clarified the taxonomic status of the species within the genus. This has allowed genetic characterisation of the taxa belonging to Trichobilharzia, the detection of a species specificity related to molluscan hosts, and determination to the species level of the furcocercariae which are the causative agents of the human disease in Europe (Dvorak et al 2002;Horak et al 2002;Rudolfová et al 2005;Aldhoun et al 2009;Schets et al 2010;Jouet et al 2010).…”
Section: Introductionmentioning
confidence: 98%